Comparative analysis of SD biosensor standard™ M10 HPV and seegene anyplex™ II HPV HR for detecting high-risk human papillomavirus: a concordance study - Abigail Rembui, Jerip; Vaenessa, Noni; Vanessa Kiah, Anthony; Andy Bong, Cheong Shin; Jaria, Adam; Tan, Cheng Siang (BioMed Central Ltd., 2025)
Background Cervical cancer, primarily caused by persistent high-risk human papillomavirus (hrHPV) infections, is a significant health burden, particularly in low-resource settings such as Sarawak, Malaysia. Effective prevention depends on effective vaccination and early hrHPV detection. This study compares the performance of the point-of-care test (POCT) SD Biosensor Standard™ M10 HPV and laboratory-based Seegene Anyplex™ II HPV HR assay, focusing on their ability to detect and genotype hrHPV in self-collected high vaginal swab samples.